Insight and Outlook – A Review of the Royal Society of Chemistry’s Open Access Program - Popov, Mikhail (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. To support the transition to Open Access (OA ), the Royal Society of Chemistry introduced the Gold for Gold initiative in 2012, rewarding all institutions subscribing to RSC Gold with voucher codes to make papers available via OA, free of charge. The ‘Gold for Gold’ scheme started as a pilot for the UK only and was rolled out to universities and research institutes in the rest of the world in 2013. In 2015 more than 700 customers qualified for this project and over 10,000 voucher codes were issued. We will provide background information and figures about the usage of the vouchers and acceptance of the project. We will review if there is a traceable record of success, what effect the Gold for Gold project has on the RSC publications, if there is any measurable global impact; and finally what changes to expect in the future. With this presentation we want to support and add to the discussion around transition to Open Access, to promote Open Science and encourage further development of open access policies.